Courage, Justice, and Practical Wisdom as Key Virtues in the Era of COVID-19 - Fowers, Blaine J.; Novak, Lukas F.; Calder, Alexander J.; Sommer, Robert K. (Frontiers in Psychology, 2021)
B. Fowers, Richardson, and Slife (2017) recently made a general argument for virtues as the characteristics necessary for individuals to flourish, given inherent human limitations. For example, people can flourish by developing the virtue of friendship as they navigate the inherent (healthy) human dependency on others. This general argument also illuminates a pathway to flourishing during the COVID-19 pandemic, the risks of which have induced powerful fears, exacerbated injustices, and rendered life and death decisions far more common. Contexts of risk and fear call for the virtue of courage. Courage has emerged more powerfully as a central virtue among medical personnel, first responders, and essential workers. Longstanding inequalities have been highlighted during the pandemic, calling for the virtue of justice. When important personal and public health decisions must be made, the central virtue of practical wisdom comes to the fore. Wise decisions and actions incorporate the recognition of relevant moral concerns and aims, as well as responding in fitting and practical ways to the specifics of the situation. Practicing courage, justice, and practical wisdom illuminates a path to flourishing, even in a pandemic.